The Relationship Between Knowledge and Attitudes About Balanced Nutrition and Nutritional Status Among 10th Grade Students at State High School 1 Palangka Raya - Listy Try Memei; Riska Ovany; Merry Delyka (PROMOTOR, 2026)
Background: Adolescents are a group undergoing rapid growth and development, which requires a balanced nutritional intake. A lack of knowledge and a negative attitude toward balanced nutrition can be a risk factor for nutritional problems, including both undernutrition and overnutrition. According to WHO in 2021, around 196 million adolescents worldwide experienced undernutrition, and more than 340 million children and adolescents were obese. Objective: This research aims to determine the correlation between knowledge and attitude about balanced nutrition with the nutritional status of 10th-grade students at SMA Negeri 1 Palangka Raya.Methods: This research used a correlational design with a cross-sectional approach. A total sample of 228 students was selected using proportional random sampling. The research instruments included a questionnaire to assess knowledge and attitudes, and anthropometric measurements using Body Mass Index (BMI) to assess nutritional status. Data were analyzed using the Spearman Rank test. Results: There was a significant correlation between knowledge about balanced nutrition and nutritional status (p value < 0.042). However, there was no significant correlation between attitude and nutritional status (p value > 0.951). Conclusion: There is a significant correlation between knowledge of balanced nutrition and nutritional status among tenth-grade students at SMA Negeri 1 Palangka Raya. Students with better knowledge tend to have better nutritional status, as adequate understanding encourages healthier food choices. However, there is no significant correlation between attitude and nutritional status. Although most respondents had a positive attitude, it was not always reflected in actual behavior. External factors such as family environment, availability of healthy food, and daily habits also influence overall nutritional status.